Coupled macroscale-microscale model for hydrogen embrittlement in polycrystalline materials. (19th February 2015) - Jothi, S.; Croft, T.N.; Brown, S.G.R.
Abstract Prediction of hydrogen embrittlement within a component requires the influence of several length scales to be accounted for. The loads that affect the rate of hydrogen diffusion, typically thermal and structural, derive from the macro or component scale. Micro-structural analysis has an important role to play in providing accurate estimates of the typically homogenous material characteristics employed at the component scale. This contribution considers the coupling of a micro-scale model with the component scale. A micro-scale model is employed in critical regions of the component where resolution of the heterogeneous behaviour is necessary. A tie boundary/cut boundary technique is introduced to couple the micro-scale model to the macro-scale model. The developed technique offers a computationally efficient procedure to analyse the multi-scale inter-granular hydrogen embrittlement in a polycrystalline material. This work is targeted at the prediction of hydrogen embrittlement in pulse-plated nickel and is carried out within the context of the EU FP7 MultiHy project.